Transition-metal-free decarbonylation–oxidation of 3-arylbenzofuran-2(3H)-ones: access to 2-hydroxybenzophenones - Dhotare, Bhaskar B.; Kanojia, Seema V.; Sakhiya, Chahna K.; Wadawale, Amey; Goswami, Dibakar (Beilstein Journal of Organic Chemistry, 2024)
A transition-metal-free decarbonylation–oxidation protocol for the conversion of 3-arylbenzofuran-2(3H)-ones to 2-hydroxybenzophenones under mild conditions has been developed. NMR studies confirmed the role of in-situ-generated hydroperoxide in the conversion. The protocol was applied to a diverse range of substrates to access the target products in good to excellent yields. A structure–activity study for the 5-substituted-2-hydroxybenzophenones towards UV-protection abilities has been verified by mathematical calculations.
Keywords: decarbonylation–oxidation; hydroperoxide; 2-hydroxybenzophenone; transition-metal-free; UV-protection